Conceptual Model Construction of Customer Satisfaction Affected by Responsible Supply Chain Management of Fresh Food E-commerce Platforms in China - Ke, Xiao Hua; Pinmanee, Saichon (My University, 2025)
It was found that companies which were more consumer-conscious and actively take on social responsibilities could achieve greater corporate value in previous researches. The significances of supply chain management from the perspective of customers have been emphasized by connecting RSCM with CSI. What’s more, the way the classic model of European Customer Satisfaction Index fit for the specific conditions of fresh food e-commerce platforms in China has also been studied. European Customer Satisfaction Index (ECSI) has been adopted in this research as a conceptual model base plus trust to study how the theories of Customer Social Responsible (CSR), Supply Chain Management (SCM), and Responsible Supply Chain Management (RSCM) apply for the empirical studies of fresh food e-commerce platforms in China. In the model exogenous variables were defined as the following four variables: Image, Expectation, Hardware, and Software. Endogenous variables were defined as the following two variables: Perceived Value and Customer Satisfaction. The future research will try to investigate the concerned factors in this model and finally find out the suitable factors which will affect the RSCM and customer’s satisfaction in the fresh food e-commerce. Meanwhile, the research results will offer some pragmatic and pervasive suggestions to those fresh food e-commerce companies in China and their business strategies of supply chain management.
Keywords: Customer satisfaction; Customer social responsibilities; European Customer Satisfaction Index; Fresh food e-commerce; Responsible supply chain management